Analysis of The Question Items in The Sejarah Kebudayaan Islam Book of Class IX MTs - Sukmara, Ghina Fadlilah (Jurnal Keprofesian Guru Keagamaan, 2023)
This study aims to analyze the characteristics of Competency Test questions in the book of Islamic Cultural History (SKI) grade IX Madrasah Tsanawiyah Curriculum 2013 reviewed from a cognitive level based on the revised Bloom taxonomy. This study uses a qualitative approach with a documentation study method. The research data is in the form of all Competency Test questions contained in the SKI class IX book, which consists of 70 multiple-choice questions and 35 description questions spread across seven chapters. The data analysis technique was carried out by classifying each question item into cognitive levels C1–C6, then grouping the questions into the categories of Lower Order Thinking Skills (LOTS), Middle Order Thinking Skills (MOTS), and Higher Order Thinking Skills (HOTS). The results of the study showed that the question items in the SKI class IX book were dominated by questions at the cognitive level C1 (remembering) and C2 (understanding). Some of the questions have reached the HOTS level, especially at the C4 level (analyzing) to C6 (creating), but the number is still relatively limited and not evenly distributed in each chapter. These findings indicate that the quality of the Competency Test questions in the book still needs to be improved, especially in the development of questions that encourage students' high-level thinking skills. Therefore, efforts are needed to improve and enrich the preparation of question items to be more in line with the demands of 21st century learning and to strengthen students' critical thinking skills.